2022
DOI: 10.1016/j.ynstr.2022.100427
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, neurochemical, and neuroimmune changes associated with social buffering and stress contagion

Abstract: Social buffering can provide protective effects on stress responses and their subsequent negative health outcomes. Although social buffering is beneficial for the recipient, it can also have anxiogenic effects on the provider of the social buffering – a phenomena referred to as stress contagion. Social buffering and stress contagion usually occur together, but they have traditionally been studied independently, thus limiting our understanding of this dyadic social interaction. In the present study, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 122 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…Oxytocin, on its side, has been widely demonstrated to be a critical modulator of fear and anxiety (Jurek and Neumann, 2018), which in the vast majority of cases, elicits anxiolytic effects (see Jang et al (2021); Chun et al (2022)). Thus, in agreement with this, results from our laboratory (de la Mora et al, 2016) showed that oxytocin infusion (above 25 ng/side) into the CeA triggered anxiolytic effects in rats when using the shock-probe burying test.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin, on its side, has been widely demonstrated to be a critical modulator of fear and anxiety (Jurek and Neumann, 2018), which in the vast majority of cases, elicits anxiolytic effects (see Jang et al (2021); Chun et al (2022)). Thus, in agreement with this, results from our laboratory (de la Mora et al, 2016) showed that oxytocin infusion (above 25 ng/side) into the CeA triggered anxiolytic effects in rats when using the shock-probe burying test.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, these effects often depend on specific individual characteristics of the subjects [46]. It is beyond the scope of the present review to address all these pathways; there are excellent reviews about this topic (for example, [53]).…”
Section: An Overview Of Neuroimmune Effects Of Stress Exposurementioning
confidence: 99%